Development of the Learning Media Video Tutorial "Tatak Menapu Kopi" in Arts and Culture Subjects for Dance Learning - Hasanah Nadeak; Abdil Hasan Saragih; R. Mursid (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to produce a learning media product called "Tatak Menapu Kopi" video tutorial for the Arts and Culture learning subject for dance learning at SMP Negeri 2 Siempat Nempu Hulu, Dairi Regency that is feasible, practical, and effective. This research uses a research and development (R&D) research model with research subjects totaling 35 students of IX SMP Negeri 2 Siempat Nempu Hulu, Dairi Regency, consisting of 5 students in individual tests, 10 students in small group tests, and 35 students in limited field tests. This research also involved validators from two learning media experts, two learning design experts, and two learning material experts. The results of this research explain that: (1) Through validation results by learning material experts, an average validity result of 94.7% was obtained in the very feasible/practical category; (2) validation results by learning design experts obtained an average validity result of 94.9% in the very feasible/practical category; and (3) validation results by learning media experts obtained an average validity result of 93.9% in the very feasible/practical category. (2) The results of the practicality test of the Video Tutorial "Tatak Menapu Kopi" learning media in the arts and culture learning subject for learning dance at SMP Negeri 2 Siempat Nempu Hulu, Dairi Regency show a level of practicality with a percentage of 89.1%, in the very practical category. (3) The effectiveness of using the products developed in learning is considered quite effective; this is shown by the results of the N-Gain score effectiveness test, which obtained an average value of 61.2%